Saints’ Heritage and the Egyptian Urban Forms Through History - Abdalla, Yassmein Hamdy Mohamed (Resourceedings, 2018)
When examining the traditional Egyptian community since the beginning of time, it would be found that the Egyptian individual is no different from any other traditional one. His life images and perceptions have some strong collective roots, they interweave strongly with the religion. He uses religious references to formulate images and manifestations to create a sacred universe where he can inhabit and function. The aim of this paper is to analyze vernacular/ traditional Egyptian architecture and its religious/cultural manifestations through the Egyptian heritage. It will focus on the cultural heritage of “Saints” and how they affected both traditional architecture and urban through time. This paper will cover the following: Presenting several psychological concepts in relation to the Egyptian vernacular urban forms. It will focus on the psychological Jungian concepts of “center of the world, Axis Mundi and sacred orientations”. It will also investigate their corresponding anthropological concept of the “sacred hero” which has its manifestations in the innumerous number of the Egyptian saints / “Awliaa” through history. Transcending the limitations of perspective by analyzing the urban product of a number of Egyptian case studies in the light of psychological and anthropological concepts to lay out certain popular principles and constraints that control their urban manifestation. Exploring The huge legacy of Saints/ Awliaa with all their related festive ceremonies as this collective belief of saints leads to an important socio-cultural event that is held in most of Egyptian urban settlements. It is “Al-Moulid”, a religious ceremonial festival that is held to celebrate the birth of the saints. These religious ceremonies have a strong role in formulating the Egyptian cultural and religious identities. Finally, presenting a classification for the Egyptian villages and cities on corresponding to this cultural / religious heritage and their manifestations on the Egyptian urban forms.